Analisis Kestabilan Lereng Tambang Menggunakan Metode Janbu Simplified Dengan Pendekatan Probabilitas Kelongsoran Pada PLB Front IV Batukapur IUP OP 206,96 Ha PT. Semen Padang, Indarung, Provinsi Sumatera Barat - Dewi Suryani; Bambang Heriyadi (Journals Mining Engineering : Bina Tambang, 2022)
PT. Semen padang is a limestone mining company which is materials for cement manufacturing in lubuk kilangan, padang city. Ore is extracted by open pit mining method with a side hill type system, which is an open mining method that is applied to mine rocks located on hillsides or in the form of hills. The plb (point loading barat) area is one of an activity area for the limestone loading process in iup op 206.96 ha. The mining process causes the rock mass become unstable and has the potential for slope failure.The results of the actual slope analysis using method simplified janbu, the value of the safey factor (SF) is 1.05 and the probability of failures (PF) is 14.6%. And the saturated slope has a safey factor (SF) value is 0.8 and the probability of failures (PF) is 100%. Recommendations of slope geometry based on the results of slide 6.0 software analysis obtained a safety factor (fk) is 1.37 and the probability of failure (PF) is 0.00%. While in  saturated condition the result of  safety factor (fk) is 1.36 and probability of failure (PF)  is 0.00% with a slope height of 70.7 m and a slope of 42°. Based on the sensitivity plot graph, the material that affects the slope stability of plb front IV PT. Semen padang is the cohesion input material (c).